Autologous stem cell transplant for high‐risk neuroblastoma: Achieving cure with low‐cost adaptations. Issue 6 (20th March 2020) - Jain, Richa; Hans, Rekha; Totadri, Sidharth; Trehan, Amita; Sharma, Ratti Ram; Menon, Prema; Kapoor, Rakesh; Saxena, Akshay Kumar; Mittal, Bhagwant Rai; Bhatia, Prateek; Kakkar, Nandita; Srinivasan, Radhika; et al.
Abstract: Background:  The majority of patients in low‐ and middle‐income countries (LMIC) are unable to receive optimal therapy, including autologous stem cell transplant (ASCT) for high‐risk neuroblastoma. Management is intensive and multidisciplinary; survival is often poor. We report a single‐center outcome of high‐risk neuroblastoma, with adaptations optimized for LMIC. Procedure:  The study was retrospective. Patients were treated on the backbone of the high‐risk neuroblastoma study‐1 of SIOP‐Europe (HR‐NBL1/SIOPEN) protocol with ASCT. Adaptations incorporated to decrease cost, requirement for inpatient admission, infections, and faster engraftment included (a) optional outpatient administration for rapid‐COJEC, (b) two sessions of stem‐cell apheresis, (c) storing stem cells at 2‐6°C without cryopreservation for up to 7 days, (d) no central lines, (e) no antibacterial/antifungal/antiviral prophylaxis, (f) omitting formal assessment of cardiac/renal/pulmonary functions before ASCT, and (g) administration of pegylated granulocyte colony‐stimulating factor on Day +4. Results:  Over 5 years 9 months, 35 patients with high‐risk neuroblastoma were treated. Rapid‐COJEC was administered over a median duration of 80 days (interquartile range: 77, 83). Conditioning regimen included melphalan (n = 7), oral busulfan‐melphalan (Bu/Mel; n = 6), or intravenous Bu/Mel (n = 22). The median viability of stem cells stored for 6 days (n = 28) was 93% (range: 88‐99). Two (5.7%) patients had ASCT‐related mortality. The 3‐year overall and event‐free survival was 41% and 39%, respectively. A relapse occurred in 20 (57%) patients. Treatment abandonment was observed in one (3%) patient. Conclusions:  Administration of therapy in a disciplined time frame along with low‐cost adaptations enables to manage high‐risk neuroblastoma with low abandonment and an encouraging survival in LMIC. Stem cells can be stored safely without cryopreservation for up to 7 days.